"Polisi RW" it’s effective in crime prevention? experience Metro Jaya Police Department, Indonesia - Rimawan, Dany; Payasan, Lalu Guntur (Technium Social Sciences Journal, 2023)
The rise of crime after the Covid-19 pandemic in Jakarta, Jakarta's position as the capital of Indonesia and the transformation of precision police spawned the concept of Polisi RW adapted from community policing, hotspot policing and predictive policing. Polisi RW are expected to be able to conduct crime prevention efforts in the Metro Jaya Regional Police Work Area. The purpose of this study is to test the effectiveness of Polisi RW in reducing the number of crimes and accelerating crime reporting services handled at Metro Jaya Police Department. A quasi-experimental one group pre-post test was selected to test the application of Polisi RW in crime prevention with indicators of reduced crime. The data used in this study is data on the number of crimes reports in the January-February 2023 period as pre and as post period March-April 2023. In addition to the difference between the pre and post ranges, researchers also took measurements in the period March-April 2022 with March-April 2023 as comparison data. Paired sample t-test is used to determine the difference and Cohen’s effect size to determine the magnitude of the effect of Polisi RW intervention. Test results on differences in the number of crime reports for the period before and after the implementation of Polisi RW p-value = 0.046, Cohen’s effect size of 0.451; The number of crime reports for the period March-April 2022 with March-April 2023 was found to be p=value 0.003, Cohen's d= 1.158. There is an influence of Polisi RW on crime prevention and acceleration of the process of solving crime reports in the Metro Jaya police department. Re-measurement is required after 6 months of application.